2004
DOI: 10.1016/j.ejvs.2003.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Aneurysm and its Correlation to Plasma Homocysteine, and Vitamins

Abstract: This study confirms significantly higher levels of plasma homocysteine in AAA patients but lower levels of B12. Use of supplemental vitamins that should lower plasma homocysteine may modify vascular disease progression. Clinical trials in this direction are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 33 publications
5
34
1
2
Order By: Relevance
“…Schumacher and co-workers observed an association between aneurysms of the abdominal aorta and ocular exfoliation [36]. On the other hand, later, a high incidence of elevated Hcy levels was found in patients who suffered an abdominal aortic aneurysm [38,50].…”
Section: Introductionmentioning
confidence: 93%
“…Schumacher and co-workers observed an association between aneurysms of the abdominal aorta and ocular exfoliation [36]. On the other hand, later, a high incidence of elevated Hcy levels was found in patients who suffered an abdominal aortic aneurysm [38,50].…”
Section: Introductionmentioning
confidence: 93%
“…An emerging pattern of atherosclerosis was detected in these patients and it was concluded that genetic defects in homocysteine metabolism and associated homocysteinuria was responsible for these vascular lesions (Guilliams, 2004). Endothelial vascular injury and atherosclerosis was subsequently demonstrated through intravenous infusion of Hcy in an animal model (Warsi et al, 2004). Several studies followed this, reporting the association between Hcy concentrations and vascular disease and more recent large scale meta-analyses have supported these findings (Castro et al, 2006).…”
Section: Historical Perspectivementioning
confidence: 64%
“…Hcy can also be metabolised to cystathionine, an intermediate of the non-essential amino acid cysteine. Vitamin B6 is necessary for this transulphuration reaction to occur ( Figure 1) (Warsi et al, 2004;Guilliams, 2004;Moroz et al, 2007;Castro et al, 2006) Excess levels of Hcy are excreted to the plasma where the liver and kidney are the organs achieving catabolism and excretion of Hcy. Despite this, mild hyperHcy is present in 5-7% of the general population, due to either inherited or acquired dietary deficiencies of vitamin B6, B12 and folic acid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations